2006
DOI: 10.1080/14622200600670389
|View full text |Cite
|
Sign up to set email alerts
|

Are menthol cigarettes a starter product for youth?

Abstract: This study assessed the relationship between menthol use and nicotine dependence. Data from the National Youth Tobacco Survey indicated that menthol cigarette use was significantly more common among newer, younger smokers. Additionally, youth who smoked menthol cigarettes had significantly higher scores on a scale of nicotine dependence compared with nonmenthol smokers, controlling for demographic background and the length, frequency, and level of smoking. The study suggests that menthol cigarettes are a start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
122
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 28 publications
7
122
1
3
Order By: Relevance
“…These findings are consistent with findings by Hersey et al (2006) of current middle school and high school smokers in the 2000 and 2002 National Youth Tobacco Surveys. Menthol cigarette smokers (n = 1,552; 48.5%) in the sample were younger newer smokers than those smoking nonmenthol cigarettes (n = 1,650; 51.5%).…”
Section: Menthol Cigarettes and Measures Of Nicotine Addictionsupporting
confidence: 90%
“…These findings are consistent with findings by Hersey et al (2006) of current middle school and high school smokers in the 2000 and 2002 National Youth Tobacco Surveys. Menthol cigarette smokers (n = 1,552; 48.5%) in the sample were younger newer smokers than those smoking nonmenthol cigarettes (n = 1,650; 51.5%).…”
Section: Menthol Cigarettes and Measures Of Nicotine Addictionsupporting
confidence: 90%
“…Furthermore, menthol cigarettes are increasingly shown to promote nicotine dependence and adversely impact smoking cessation, especially among sub-populations of smokers, e.g., African-Americans or women [3,29,43,50,51]. Recent nationally representative studies in the USA and Canada [49, [51][52][53][54][55][56][57][58][59][60] have confirmed earlier reports [61][62][63][64][65][66][67][68][69] that menthol cigarette use is associated with increased nicotine addiction and reduced cessation success. Other studies, however, failed to demonstrate a significant difference in cessation-related outcomes between menthol and nonmenthol cigarette smokers [26, [70][71][72][73][74].…”
mentioning
confidence: 63%
“…Youth who initiate smoking with a menthol-flavored tobacco product are more likely to progress to dependence and to report higher levels of dependence. 73,74 RECOMMENDATIONS TO PROTECT CHILDREN FROM TOBACCO SMOKE AND NICOTINE EXPOSURE…”
Section: Tobaccomentioning
confidence: 99%